2020
DOI: 10.37398/jsr.2020.640127
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Comparative Analysis of Simple Sequence Repeats in Chloroplast Genomes of Genus Nymphaea

Abstract: Simple sequence repeats (SSRs) also known as microsatellites, found in almost all organisms, are one of the widely used genetic markers. Despite the availability of a number of chloroplast genome of genus Nymphaea the information about its chloroplast SSR (cpSSR) is not well understood. In the present study, a total of 96 cpSSRs were mined in 6 chloroplast genome of genus Nymphaea (N. alba, N. ampla, N. capensis, N. jamesoniana, N. lotus, and N. mexicana). Mononucleotides (33, 34.38%) were most abundant follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Earlier, mtSSRs were identified in various plants including order Hypnales (Anand et al, 2019), Aneura pinguis (L.) Dumort (Kumar & Shanker, 2020a), and Orthotrichum (Kumar et al, 2020). Apart from these, SSRs were also mined in chloroplast genomes of Arabidopsis (Kumar & Shanker, 2018a) and Nymphaea (Kumar & Shanker, 2020c). In all these studies, the distribution of mono-/hexanucleotide repeat motifs also varied from species to species, which is congruent with the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier, mtSSRs were identified in various plants including order Hypnales (Anand et al, 2019), Aneura pinguis (L.) Dumort (Kumar & Shanker, 2020a), and Orthotrichum (Kumar et al, 2020). Apart from these, SSRs were also mined in chloroplast genomes of Arabidopsis (Kumar & Shanker, 2018a) and Nymphaea (Kumar & Shanker, 2020c). In all these studies, the distribution of mono-/hexanucleotide repeat motifs also varied from species to species, which is congruent with the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Other repeat motifs and identical repeat motifs showing no significant similarity of flanking sequences with any of the species in the same genus were considered as unique microsatellites (Kumar & Shanker, 2020a, 2020c. A schematic representation to detect common, polymorphic, and unique microsatellites is presented in Fig 4.…”
Section: Detection Of Common Polymorphic and Unique Mtssrsmentioning
confidence: 99%
“…In the chloroplast genome, microsatellites or SSRs distributed in the genome with the length of almost 1 bp to 6 bp. Previously many studies reported SSRs at different positions in chloroplast genomes 55,56 . In the present study, SSRs distributed at different locations such as IR regions, LSC and SSC region were identified in the A. marina.…”
Section: Discussionmentioning
confidence: 99%